2022
DOI: 10.3390/ma15103678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic, Structural and Molecular Docking Studies of Some New Nano-Sized Ferrocene-Based Imine Chelates as Antimicrobial and Anticancer Agents

Abstract: The newly synthesized organometallic acetyl ferrocene imine ligand (HL) was obtained by the direct combination of 2-acetyl ferrocene with 2-aminothiophenol. The electronic and molecular structure of acetyl ferrocene imine ligand (HL) was refined theoretically and the chemical quantum factors were computed. Complexes of the acetyl ferrocene imine ligand with metal(II)/(III) ions (Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II)) were fabricated. They were inspected by thermal (DTG /TG), spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…This observation was inversed with Gram-negative bacteria as BHX mixed ligand complexes were highly active than ofloxacin-based metal complexes. 14 ((Z)-cyclopenta-1,3-dien-1-yl(2-(1-((3-hydroxyphenyl) imino)ethyl)cyclopenta-2,4-dien-1-yl)iron) and its metal chelates were prepared by Mai et al 37 and tested against different strains of Gram-positive and Gram-negative bacteria. Generally, it was observed that the BHX mixed ligand complexes are highly more reactive as antibacterial agents than ferrocene-based Schiff base metal complexes.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was inversed with Gram-negative bacteria as BHX mixed ligand complexes were highly active than ofloxacin-based metal complexes. 14 ((Z)-cyclopenta-1,3-dien-1-yl(2-(1-((3-hydroxyphenyl) imino)ethyl)cyclopenta-2,4-dien-1-yl)iron) and its metal chelates were prepared by Mai et al 37 and tested against different strains of Gram-positive and Gram-negative bacteria. Generally, it was observed that the BHX mixed ligand complexes are highly more reactive as antibacterial agents than ferrocene-based Schiff base metal complexes.…”
Section: Compoundmentioning
confidence: 99%
“…Generally, it was observed that the BHX mixed ligand complexes are highly more reactive as antibacterial agents than ferrocene-based Schiff base metal complexes. 37…”
Section: Compoundmentioning
confidence: 99%
“…With continued interest in organic synthesis, it was desirable to identify efficient and effective synthesis methods due to their wide range of pharmacological actions. Antibiotics [ 26 ], anti-inflammatory medications [ 27 ], muscle relaxants [ 28 ], ant tubercular drugs [ 29 ], and antiviral agents [ 30 ] are only a few of the drugs that contain this backbone. Unfortunately, the virus’s rapid spread resulted in a significant rate of mortality and morbidity over the globe [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases are promising chelating ligands in coordination chemistry due to their propensity to develop stable chelates with transition metals [ 1 , 2 , 3 , 4 , 5 , 6 ]. Schiff base metal chelates were widely investigated due to their amazing chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%